2017
DOI: 10.1016/j.mee.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of isopropanol on gold assisted chemical etching of silicon microstructures

Abstract: Wet etching is an essential and complex step in semiconductor device processing. Metal-Assisted Chemical Etching (MacEtch) is fundamentally a wet but anisotropic etching method. In the MacEtch technique, there are still a number of unresolved challenges preventing the optimal fabrication of highaspect-ratio semiconductor micro-and nanostructures, such as undesired etching, uncontrolled catalyst movement, non-uniformity and micro-porosity in the metal-free areas. Here, an optimized MacEtch process using with a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…It has been reported that Si porosity increases with increasing the Si doping and it can be controlled by the etching composition. 60,61 Hildreth et al noted that MacEtch with vapour HF occurs with a lack of any microporous and mesoporous silicon etch front. According to this relevant observation, we used h100i n-type Si wafers with low resistivity (0.001-0.01 O cm) in order to maximize the etching rate.…”
Section: Etching Mechanismmentioning
confidence: 99%
“…It has been reported that Si porosity increases with increasing the Si doping and it can be controlled by the etching composition. 60,61 Hildreth et al noted that MacEtch with vapour HF occurs with a lack of any microporous and mesoporous silicon etch front. According to this relevant observation, we used h100i n-type Si wafers with low resistivity (0.001-0.01 O cm) in order to maximize the etching rate.…”
Section: Etching Mechanismmentioning
confidence: 99%
“…New etching-based techniques (metal-assisted chemical etching: Romano et al (2016Romano et al ( , 2017, Bosch etching with seedless gold electroplating: Jefimovs et al (2017), Kagias et al (2019)) were attempted but failed to produce prototype gratings of functional thickness. However, success was found with the LIGA (X-ray lithography, electroplating and moulding) method employed by MicroWorks GmbH.…”
Section: The Engineering Model Gridsmentioning
confidence: 99%
“…Since its discovery in 2000, by Li et al [13], MacEtch of silicon has emerged as a new technique capable of fabricating 3D nano-and micro-structures of several shapes and applications [23]:-nano-porous film, nanowires [24], 3D objects [25], trenches, vias [26], micro-fins [27], nano-scale grooves, surface antireflection texturing [28], optoelectronic devices such as solar cells [29] and photodetectors [30], sensor devices [31], X-ray optics-in a few semiconductors substrates: Si [15], Ge [30], poly-Si [32], GaAs [33], β-Ga 2 O 3 [27], SiC [34], etc.-and different catalysts: Ag, Au, Cu, Pt, and Pd [15]. MacEtch has been developed with a strong controlled vertical directionality with respect to the substrate and successfully applied for producing X-ray zone plates [17,23,[35][36][37][38] and diffraction gratings [19,20,37,[39][40][41]. In MacEtch, a catalyst layer (e.g., Au) is patterned onto the substrate (e.g., Si) to locally increase the dissolution rate of the substrate material in an etchant solution including a fluoride etchant such as hydrofluoric acid (HF) and an oxidizing agent such as hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%